FV 2 A new neurophysiological test protocol for the assessment of the somatosensory nervous system – from the laboratory to clinical application. (May 2022) - Hüllemann, P.; Fabig, S.C.; Kersebaum, D.; Lassen, J.; Sendel, M.; Jendral, S.; Muntean, A.; Baron, R.
Abstract : During clinical routine diagnostics, the integrity of the somatosensory nervous system is assessed by somatosensory-evoked potentials (SEPs), analyzing Aβ-fiber function, the posterior funiculus, brainstem, and the somatosensory cortex (Muzyka and Estephan 2019). Nevertheless, SEPs cannot provide diagnostic information on small fibers (Cruccu et al. 2004), which form around 80% of the somatosensory nervous system. These small fibers are subdivided into heat-sensitive Aδ-fibers (AMH II), mechanosensitive Aδ-fibers (AMH I), cold-sensitive Aδ-fibers, and C-fibers (mediating noxious and warm stimuli; Gasser 1941). Therefore, a combination of specific tests is required to gain a complete electrophysiological assessment of the somatosensory nervous system or to detect loss of function for specific nerve fiber subtypes. Loss of function of specific subtypes of somatosensory nerve fibers are found in neuropathic disorders, such as polyneuropathy (Bönhof et al. 2017), radiculopathy (Carlstedt 2008; Cavanaugh et al. 1997), traumatic nerve injury (Rotshenker 2011), and others (Gomatos and Rehman 2021). Large-fiber neuropathies only affect thickly myelinated nerve fibers (such as hypocobalaminemia-associated neuropathies; (Franques et al. 2019; Stabler 2013)), while other neuropathic disorders begin by an affection of small fibers (Aδ- and C-fibers), such as chemotherapy-induced polyneuropathy (Timmins et al. 2020). Some neuropathies involve specific subtypes of small nerve fibers, such as a loss of function of cold-mediating Aδ-fibers during the early stage of Fabry's disease (Onishi and Dyck 1974). Here, we present a novel neurophysiological test protocol, which assesses a major part of the somatosensory nervous system by recording evoked potentials of touch, pinprick, vibration, heat/heat pain, cold, and warm stimuli. This test protocol was applied on healthy subjects in a first step and then transferred to patients with painful radiculopathy and painful polyneuropathy in a second step. The EP-measurements were compared to clinical data, nerve conduction studies as well as Quantitative Sensory Testing. We found several promising analogies to clinical features of the tested patients, which motivates us and hopefully other researchers to continue on this path with the goal to form a reliable and valid electrophysiological sensory tool that could be used as an outcome measure for future neurophysiological studies and in clinical routine diagnostics.